Ferroelectric and dielectric behaviour of MWCNT/poly urethane composite. (2022) - Chaurasia, Amit; Dwivedi, U.K.; Hashmi, S.A.R.
Abstract: This study includes the fabrication of multi walled CNT reinforced polyurethane composite (MWCNT/PU) which are characterized for Ferroelectric and dielectric behaviour. Ferroelectric property (P-E loop and I-V curve) leakage current behavior of MWCNT/PU composite were studied using P-E loop tracer. It is found that electric Polarization depends on the frequency because of mass associated with the change in the dipole. Leakage current behavior is analyzed and discussed. Dielectric parameters like Dielectric constant and Dissipation factor were studied at different temperature (30–70 °C) through LCR meter. It is found that the dielectric constant and dissipation factor increased as temperature increases. The dissipation factor increases with frequency and temperature.